Monitoring the Vibration Response of a Tunnel Boring Machine for Real Time Detection of Geological Conditions - duanyai, sasi; Arangjelovski, Goran (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
During tunnel excavation, unexpected geological conditions and changes in the advancing direction present geological hazards and challenging problems during tunnel construction. In the study, real-time vibration monitoring is carried out on the surrounding rock during the excavation process using a tunnel boring machine (TBM) to study the changes in the vibrational response and geological conditions. The monitoring is performed on the Mae Tang - Mae Ngad - Mae Kuang Diversion Tunnel Project in Northern Thailand which is excavated using a TBM. The diameter of the tunnel is 4.74 meters, and the excavation is in general in rock conditions. The monitoring system consists of geophone sensors mounted on the Tunnel Boring Machine and on the segmented wall. Subsequently, velocity time histories are analyzed in the time domain and spectral frequency domain. The TBM vibrations during excavation in hard rock or mixed face ground conditions (MFC) in addition to the TBM parameters are related to geological conditions and results from the monitoring suggested that the geological conditions changed during the drilling process.